ASEAN FTAS DAN LIBERALISASI PERDAGANGAN JASA : TANTANGAN JASA TENAGA KERJA BAGI INDONESIA - Pudjiastuti, Tri Nuke (Pusat Penelitian Politik, 2010)
Under contemporary globalization and liberalization particularly with many kinds ofFree Trade AgreementsÂ FTAs in terms of liberalization of services and labours Indonesia has to deal with so many challenges In oneÂ side theforeign labour mobility will increase in thefuture ofIndonesian labour market while lack of competencyÂ mostly for local or domestic labours In another side at the current situation Indonesian migrant workers are stilldominated by unskilled workers which is notpart of trade ofservices in FTAs scheme